Epistemological knowledge when Karl Popper - Razzouk, Ibrahim; Deeb, Qamar (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Karl Popper’s philosophy of science is considered a true portrayal of developments that have contributed to the development of philosophy in the twentieth century, which bridged the gap between the natural and social sciences. This rapprochement between the natural and social sciences has established Popper's philosophy, whether in the scientific method or theory of knowledge. Philosophy of Popper has raised a huge wave of support on the one hand and another wave of opposition like the various major philosophical currents, and these discrepancies in favor of the philosophy of Popper and the opposition to him raised philosophical and scientific new problems, which have enriched the philosophy of science in the twentieth century.